906 De novo mutations in childhood-onset systemic lupus erythematosus. (14th December 2022) - Baxter, Sarah K; Gulsuner, Suleyman; Eckert, Mary M; Lee, Ming K; Walsh, Tom; Stevens, Anne; King, Mary-Claire
Abstract : Background: It is well-established that genetics plays a role in the origins of systemic lupus erythematosus. Yet known genetic influences do not account for the heritability of lupus, as supported by family, twin, and migrant studies. Based on the missing heritability, further genetic testing of children with lupus is likely to strengthen the relationship of known risk genes to lupus and uncover novel risk genes. We integrate exome sequencing with a patient-parent-parent trio design to enable the identification of de novo mutations. This approach enriches for pathogenic events, including in the understudied Alaska Native population. In addition, we use long-read Nanopore sequencing to identify complex structural de novo events in these families. Methods: Patients with a diagnosis of lupus prior to age 18 and their parents were enrolled in our study, which was approved by the institutional review boards of Seattle Children's Hospital and the University of Washington. Exome sequencing was performed using DNA isolated from whole blood or saliva. Long- read whole-genome sequencing (ONT PromethION) was performed using DNA from whole blood or freshly expanded lymphoblasts. In-house pipelines were used to identify de novo events. Candidate mutations were prioritized based on in-silico analyses of pathogenicity, population rarity, and known biologic functions. Prioritized candidate mutations were evaluated for expression by qPCR and by western blot in transfected cells; activity of transcription factors was evaluated by luciferase assay. Results: Fifty-one families, ascertained on a patient with childhood-onset lupus, were sequenced to identify de novo mutations. In preliminary analysis 18 of the 51 patients were found to have promising de novo single-nucleotide variant genetic mutations. Preliminary in vitro analysis of one of these candidates, a mutation in the transcriptional repressor BACH1, suggests that the identified mutation alters protein activity: expression of HMOX1, a BACH1- regulated gene, was significantly higher in the patient compared to her parents or to unrelated controls, as measured by qPCR of whole blood; and in a luciferase assay with putative BACH1 binding sites from the HMOX1 promotor, the repressor activity of mutant BACH1 was decreased in comparison with wild-type BACH1. In addition, four of the 51 patients were found to carry previously uncharacterized de novo structural variants, including deletions of length 500kb and 1547kb, and duplications of length 786 kb and 900kb. Conclusions: We have established a pipeline for sensitive detection of de novo genetic variants in childhood-onset lupus, integrating short-read and long-read sequencing of patient-parent-parent trios. Preliminary analysis of these trios yields a high rate of promising candidate mutations, including a high percentage of patients carrying large structural mutations.